Analisis Determinan Kesehatan Keuangan BUMN Karya di Indonesia - Prasanti, Tyas Ayu; Pratama Putra, Gigih Alfrian; Puspita, Ingelia (Jurnal Manajemen Perbendaharaan, 2025)
In order to enhance competitiveness, the government focuses on infrastructure development by encouraging the participation of Construction Sector State-Owned Enterprises (SOEs). These state-owned enterprises are assigned tasks by the government, despite capital constraints, which have the potential to cause financial distress. This study employs ordinal logistic regression using the Partial Proportional Odds Model approach to identify factors influencing the financial health of Construction Sector SOEs. The analysis results indicate that financial performance, company size, and additional State Capital Injection (PMN) received by each Construction Sector SOEs significantly affect the company's financial health. This finding reaffirms the important role of the State Budget (APBN) through PMN, as a fiscal policy instrument in supporting the assignment of Construction Sector SOEs and maintaining the financial stability of strategic state-owned corporations.